Prenatal Anogenital Distance Is Shorter in Fetuses With Hypospadias. (28th November 2016) - Gilboa, Yinon; Perlman, Sharon; Kivilevitch, Zvi; Messing, Baruch; Achiron, Reuven
Abstract : Objectives: Recent research provides evidence that anogenital distance may serve as a novel metric to assess reproductive potential in men. In children, a shorter anogenital distance was linked with cryptorchidism, hypospadias, and micropenis. Scarce data exist in the literature regarding anogenital distance measurement in the fetus. The aim of our study was to assess whether intrauterine measurement of fetal anogenital distance could assist in the differential diagnosis of male genital anomalies. Methods: Anogenital distance was prospectively measured in all cases referred for suspected isolated abnormal male genitalia. Final diagnoses, confirmed by a pediatric urologist, were compared with anogenital distance prenatal measurements. Results: Fifty‐two cases were referred for evaluation because of suspected male external genital malformation during a 12‐month period. Cases with normal‐appearing genitalia, associated major malformations, and early severe fetal growth restriction were excluded from the study. Postnatal examination revealed 14 cases of hypospadias in varying severity and 8 cases of a buried penis. All fetuses with hypospadias had an anogenital distance measurement below the fifth percentile. Statistical analysis revealed a significant difference between the normal mean anogenital distance for gestational age versus those with hypospadias (mean ± SD, 16.90 ± 4.08 and 11.68 ± 3.31 mm, respectively; P = .001). No significant difference was found between the normal mean anogenital distance for gestational age versus those with a buried penis (18.85 ± 2.76 and 19.46 ± 3.41 mm; P = .700). Conclusions: Fetuses with hypospadias have a statistically significant shorter anogenital distance compared with the general population. Therefore, anogenital distance may serve as a complementary objective sonographic parameter in the prenatal assessment and counseling of male external genital anomalies.